Echinococcus multilocularis and Its Intermediate Host: A Model of Parasite-Host Interplay. (21st March 2010) - Vuitton, Dominique Angèle; Gottstein, Bruno
Abstract : Host-parasite interactions in the E. multilocularis -intermediate host model depend on a subtle balance between cellular immunity, which is responsible for host's resistance towards the metacestode, the larval stage of the parasite, and tolerance induction and maintenance. The pathological features of alveolar echinococcosis. the disease caused by E. multilocularis, are related both to parasitic growth and to host's immune response, leading to fibrosis and necrosis, The disease spectrum is clearly dependent on the genetic background of the host as well as on acquired disturbances of Th1-related immunity. The laminated layer of the metacestode, and especially its carbohydrate components, plays a major role in tolerance induction. Th2-type and anti-inflammatory cytokines, IL-10 and TGF-β, as well as nitric oxide, are involved in the maintenance of tolerance and partial inhibition of cytotoxic mechanisms. Results of studies in the experimental mouse model and in patients suggest that immune modulation with cytokines, such as interferon-α, or with specific antigens could be used in the future to treat patients with alveolar echinococcosis and/or to prevent this very severe parasitic disease.